Teknologi dan Produksi Akuakultur di Danau Tondano Kabupaten Minahasa - Mambrasar, Deni; Salindeho, Indra R.N; Tumembouw, Sipriana (Universitas Sam Ratulangi, 2014)
The aim of this study was to know theÂ applied technology and the production value of the aquaculture activities in the waters of Â Lake Tondano and to identify factors influencing aquaculture production in Tondano lake. Data collectedÂ consisted of primary andÂ sekunder data. Â Primary data Â were collected by conducting a survey to fish-farmers as respondents around the lake Tondano. Â Operational aquaculture data were obtainedÂ by interviewing the fish farmers and by observation. Â Secondary data were collected from variousÂ institution Â such as MinahasaÂ Fisheries Â OfficeÂ ,Â Office ofÂ Village Head and Fish-farmer Â GroupÂ Administrative Centre.Â Collected data were Â descriptively analyzed Â and presented in the form of tabulation and various model of diagram.Â Fluctuated data in aquacultural production valueÂ and the number ofÂ operatedÂ KJT Â during the periood of Â 2001 to Â 2014 was analysed by using linear regression Â and correlation. The aquacultral production value Â of the lake Tondano inÂ 2014 was Â estimated only 1227,3 tons /year. Â The number of operated Â KJT Â only remained 1203 units. Â The production value decreased consistentlyÂ from 2003 to 2014.Â Â Statistical analysis showed that during Â 2001-2014 there was a reduction about 1.236 ton every year in aquacultural production, and Â 607 units of operated KJT.Â There was a Â very strong correlation Â between Â time Â (year) and the Â the aquacultural production, and also between Â time (year) andÂ the number Â ofÂ operated KJT.Â There were 3 important Â factors Â influencing the aquacultural production value of lake Tondano, which were: environmental, technical and economic factor.Â Â However, the primary factor Â wasÂ â€˜economicâ€™ factor.Â The Â â€˜very high priceâ€™ of the fish formulated diet Â and Â the